2016
DOI: 10.1049/iet-its.2014.0251
|View full text |Cite
|
Sign up to set email alerts
|

Smart e‐bike monitoring system: real‐time open source and open hardware GPS assistance and sensor data for electrically‐assisted bicycles

Abstract: Abstract:The smart e-bike monitoring system (SEMS) is a platform for the real-time acquisition of usage data from electrically-assisted bikes (also called pedelecs or e-bikes). It is autonomous (runs off the bike battery), replicable (open source and open hardware), scalable (different fleet sizes) and modular (sensors can be added), so it can be used for further research and development. The system monitors location (global positioning system), rider control data (level of assistance) and other custom sensor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 14 publications
0
32
0
1
Order By: Relevance
“…The material used in this paper stems from lending these bikes to 80 commuters for six to eight week periods. The quantitative material is discussed elsewhere (Cairns et al 2017;Kiefer and Behrendt 2015). The material presented in this paper has not been previously published.…”
Section: Methodsmentioning
confidence: 99%
“…The material used in this paper stems from lending these bikes to 80 commuters for six to eight week periods. The quantitative material is discussed elsewhere (Cairns et al 2017;Kiefer and Behrendt 2015). The material presented in this paper has not been previously published.…”
Section: Methodsmentioning
confidence: 99%
“…Of these, our work is most similar to Kiefer and Behrendt [17], Fyhri and Fearnley [18], Paefgen and Michahelles [19], and Flüchter and Wortmann [20] which also focus on usage patterns. Kiefer and Behrendt collected GPS and motor assistance level data, but they emphasized developing a hardware system reusable by other research groups rather than data analysis.…”
Section: Related Workmentioning
confidence: 92%
“…As such, a lot of research might be needed to cover this new field of interest. Gorenflo et al (2017) [35], Kiefer and Behrendt (2016) [38], Fyhri and Fearnley (2015) [19], Fluchter and Wortmann (2014) [39], as well as Paefgen and Michahelles (2010) [40], focused, for instance, on usage patterns. Gorenflo et al (2017) conducted a 3-year field trial with 33 sensor-equipped e-bikes [35].…”
Section: E-bike Studiesmentioning
confidence: 99%
“…Gorenflo et al (2017) found that the students that participated in this field trial usually let their e-bike's batteries to get totally empty and charged them when the battery status was around 15-45%, while university staff members usually charged their batteries when they were above 70% [35]. Kiefer and Behrendt (2016) used GPS and motor assistance level data [38]. Fyhri and Fearnley (2015) analyzed odometer data collected by the e-bikes [19].…”
Section: E-bike Studiesmentioning
confidence: 99%